HUBUNGAN SLEEP HYGIENE DENGAN BEDTIME PROCRASTINATION PADA MAHASISWA UNIVERSITAS NEGERI PADANG - Reka Fitriani; Fauziah Taslim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Sleep hygiene is an important behavioral factor associated with healthy sleep patterns, while bedtime procrastination refers to the tendency to delay bedtime without external reasons despite being aware of its negative consequences. University students are particularly vulnerable to bedtime procrastination due to academic demands, excessive digital media use, and poor self-regulation. This study aimed to examine the relationship between sleep hygiene and bedtime procrastination among undergraduate students at Universitas Negeri Padang. A quantitative correlational design was employed involving 450 undergraduate students selected using quota sampling. Data were collected using the Adolescent Sleep Hygiene Scale (ASHS) and the Bedtime Procrastination Scale (BPS). Instrument validity was assessed using Corrected Item-Total Correlation, while reliability was evaluated using Cronbach’s Alpha. Data were analyzed using descriptive statistics, the Kolmogorov–Smirnov normality test, the linearity test, and Spearman’s Rank correlation. The results indicated that the instruments were valid and reliable (α = 0.855 for sleep hygiene; α = 0.803 for bedtime procrastination). Spearman’s correlation analysis revealed a significant relationship between sleep hygiene and bedtime procrastination (ρ = 0.476, p < 0.001), indicating a moderate association. The findings suggest that better sleep hygiene is associated with lower levels of bedtime procrastination. Therefore, promoting healthy sleep habits may help reduce bedtime procrastination and improve students’ sleep quality and overall well-being.